Diagnosis and Intensive Care in Children’s Diabetic Acidosis: an Interdisciplinary Viewpoint - Yu. S. Aleksandrovich; D. V. Prometnoy; E. E. Petryaykina; A. V. Kiyaev; V. A. Peterkova; V. V. Kopylov; P. A. Muratov; F. N. Brezgin; S. M. Stepanenko; A. V. Lazukin; K. V. Pshenisnov; A. A. Alyokhina (Общая реаниматология, 2024)
Diabetic ketoacidosis (DKA) is the main cause of death and disability in children with type I diabetes mellitus (T1DM). Children’s mortality from T1DM reaches 1% in developed countries and 13% in developing countries. The main cause of death in DKA is cerebral edema, clinical manifestations of which develop in 0.5–0.9% of children with DKA, while mortality riches 24%.Objective. Developing recommendations to prevent life-threatening complications of children with DKA using analysis of literature data and consolidated opinion of experts on the issues of intensive care in children with T1DM.Materials and methods. We analyzed and discussed studies in diagnosis and treatment of DKA in children with type 1 diabetes and 1200 literature sources since January 1970, published in Russian peer-reviewed scientiﬁc journals and international publications presented in the online repository Medline (Pubmed). The search for publications was carried out using the keywords: «children», «DKA», «DM1», «dehydration», «cerebral edema».Results. We considered issues of epidemiology, pathogenesis, clinical manifestations, diagnosis, intensive care for DKA, as well as clinical and diagnosis, treatment, prevention of cerebral edema issues in children. Limitations of the study were the small number of modern studies with a high level of evidence (randomized controlled trials, meta-analyses) over the past 5 years on DKA in children.Conclusion. Taking into account the national and international experience, joint recommendations on a consensus format were developed and formulated for the diagnosis of DKA, its leading complications and treatment recommendations for children with T1DM and DKA. Timely and accurate diagnosis of DKA, intensive therapy options based on proven therapeutic eﬃcacy, laboratory and clinical monitoring are warranted to interrupt the DKA pathogenesis, prevent the development of life-threatening conditions, and improve treatment outcomes for children with DKA.